Księga żałoby i śmierci / Marian Wańczowski, Mirosław Lenart ; współpr. nauk. Małgorzata Burzka-Janik [et al.]. - Wańczowski, Marian (Oficyna Wydawnicza Rytm, 2009)
Wydawnictwo encyklopedyczno-słownikowe.